Experience, Knowledge, and Perceived Comfort and Clinical Competency in Working With Suicidal Clients Among Vocational Rehabilitation Counselors. (October 2017) - Lund, Emily M.; Schultz, Jared C.; Nadorff, Michael R.; Galbraith, Kate; Thomas, Katie B.
Despite the well-documented elevated rates of suicidality among people with disabilities, no published research has examined rehabilitation counselors' experiences or perceived competency in suicide assessment or intervention. In the present study, we surveyed 223 vocational rehabilitation (VR) counselors from state VR offices in eight states regarding their experiences with, knowledge of, and perceived comfort with and competency in suicide assessment and intervention. Almost a quarter of participants worked with suicidal clients once a month or more, with more than half reporting working with suicidal clients at least once a year. Two thirds of participants reported having received some training related to suicide, and participants demonstrated both a good knowledge of suicide myths and facts, and a willingness to work with suicidal clients. However, most participants did not perceive themselves as being competent in core skills related to suicide assessment and intervention. These results suggest that more clinical training in suicide assessment and intervention is needed for VR counselors.